Exploring Gender Differences in English Learning Strategies Among Students at University - Najla Oktavia Efendi; Dzul Rachman; Ade Ismail Ramadhan Hamid; Yeni Rahmawati (English Language Education Department, Universitas Majalengka, 2025)
This study investigates gender-based differences in the use of English language learning strategies among students at Universitas Muhammadiyah Kalimantan Timur. Employing a mixed-methods design, the research gathered quantitative data through a modified Strategy Inventory for Language Learning (SILL) questionnaire and qualitative data via semi-structured interviews. Forty students (20 males and 20 females) participated in the survey, while four were interviewed to explore their learning experiences in depth. The findings indicate that female students employ a wider variety of strategies, particularly in metacognitive, affective, and social domains. Male students showed a preference for cognitive and compensation strategies. The study highlights the importance of gender-sensitive pedagogical approaches to enhance English learning outcomes.